I Hate the News Mar 18 - Dasgupta, Sunil (I Hate Politics Podcast, 2025)
The weekly news analysis from I Hate Politics: Maryland, Virginia, and DC find themselves in different places with their budget and economic woes. Developers ask for deregulation to bring construction activity back to the city. Montgomery County releases 2026 budget proposal that includes property tax and fee hikes. In New Market, MD, the town council passes mayoral term limits in an explosive meeting where opponents say the council violated charter amendment process. Music by Washington DC area composer Anna Rubin.
Keywords: I Hate Politics